GAYA KELEKATAN CEMAS TERHADAP PASANGAN PADA PEREMPUAN DEWASA AWAL YANG MENGALAMI FATHERLESS - Kharistya Celine Victoria; Wahyuni Kristinawati (Jurnal Psimawa : Diskursus Ilmu Psikologi dan Pendidikan, 2026)
The absence of a father figure (fatherless), either physically or emotionally, is an experience that may influence psychological development, particularly in the formation of attachment styles. This study explores the dynamics of anxious attachment toward romantic partners among emerging adult women experiencing fatherlessness. A descriptive qualitative approach was applied, with data collected through semi-structured in-depth interviews and observation. Participants were selected purposively after screening with the Experiences in Close Relationships Scale–Revised (ECR-R). From 10 initial respondents, two women aged 20–25 were chosen as the main participants. Findings reveal that fatherlessness contributes to anxious attachment in romantic relationships, reflected in a negative self-model, fear of abandonment, high emotional dependency, and difficulties in emotion regulation. Both participants showed similar patterns, though they differed in how anxiety was expressed, such as emotional intensity or repeated reassurance-seeking. These results highlight the significance of early paternal absence in shaping adult attachment and suggest implications for psychological counseling to support healthier and more secure romantic relationships.